2020
DOI: 10.7759/cureus.8427
|View full text |Cite
|
Sign up to set email alerts
|

Jejunal Enterolith: A Rare Case of Small Bowel Obstruction

Abstract: Small bowel obstruction is a common operative finding following an acute surgical admission. However, small bowel obstruction due to an enterolith is a rarer finding. Enteroliths are formed in conditions contributing to hypomotility and stasis within the gastrointestinal tract. These include Crohn's disease, strictures, and intestinal diverticulae. We present a case of small bowel obstruction due to an enterolith in an 89-year-old female. In our case, CT identified an inflamed jejunal diverticulum pre-operativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…Small bowel obstruction by an enterolith is rare [ 1 , 19 ]. It is assumed that the formation of primary enteroliths is related to intestinal stenosis due to Crohn’s disease and/or intestinal tuberculosis.…”
Section: Discussionmentioning
confidence: 99%
“…Small bowel obstruction by an enterolith is rare [ 1 , 19 ]. It is assumed that the formation of primary enteroliths is related to intestinal stenosis due to Crohn’s disease and/or intestinal tuberculosis.…”
Section: Discussionmentioning
confidence: 99%
“…While known complications include acute diverticulitis and SBO secondary to enterolith impaction, cases with both complications concurrently are infrequently reported in the literature. A review of existing literature uncovered only eight reported cases of jejunal diverticulitis with simultaneous enterolith obstruction [ 25 , [27] , [28] , [29] , [30] , [31] , [32] , [33] ], of which three involved bowel perforation ( Table 1.0 ) [ 25 , 27 , 28 ]. To the best of our knowledge, this case is unique in presenting with two sites of perforation and an obstructing enterolith.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, this case is unique in presenting with two sites of perforation and an obstructing enterolith. All reviewed cases required operative management, with various surgical approaches employed [ 25 , [27] , [28] , [29] , [30] , [31] , [32] , [33] ].…”
Section: Discussionmentioning
confidence: 99%
“…Resection is commonly performed in the presence of diverticula, severe inflammation or strictures, necrosis, and perforation [ 8 , 9 ]. The use of endoscopic retrieval or lithotripsy has also been described for duodenal enteroliths [ 10 ].…”
Section: Discussionmentioning
confidence: 99%